Gynecological organ involvement at robot-assisted radical cystectomy in females: Is anterior exenteration necessary? - Whittum, Michelle; Hussein, Ahmed Aly; Ahmed, Youssef E.; Khan, Hijab; Krasowski, Collin; Huben, Neil B.; May, Paul R.; Terakawa, Tomoaki; Li, Qiang; Guru, Khurshid A. (Canadian Urological Association Journal, 2018)
Introduction: We aimed to investigate patient and disease variables associated with gynecological organ invasion in females with bladder cancer at the time of robot-assisted radical cystectomy (RARC). Methods: We conducted a retrospective review of female patients who underwent robot-assisted anterior pelvic exenteration (RAAE) between 2005 and 2016. Patients were divided into two groups: those with gynecological organ involvement at RAAE and those without. Data were reviewed for perioperative and pathological outcomes. Kaplan-Meier method was used to depict survival outcomes. Multivariable stepwise regression analysis was performed to identify predictors of gynecological organ involvement. Results: A total of 118 female patients were identified; 17 (14%) showed evidence of gynecological organ invasion at RAAE. Patients with gynecological organ invasion had more lymphovascular invasion at transurethral resection of bladder tumour (TURBT) (82% vs. 46%; p=0.006), trigonal tumours at TURBT (59% vs. 18%; p=0.001), multifocal disease (65% vs. 33%; p=0.01), pN+ (71% vs. 22%; p<0.001), positive surgical margins (24% vs. 4%; p=0.02), and they less commonly demonstrated pure urothelial carcinoma at TURBT (18% vs. 66%; p<0.001). On multivariate analysis, significant predictors of gynecological organ invasion were pN-positive disease (odds ratio [OR] 6.48; 95% confidence interval [CI] 1.64–25.51; p=0.008), trigonal tumour location (OR 5.72; 95% CI 1.39–23.61; p=0.02), and presence of variant histology (OR 18.52; 95% CI 3.32–103.4; p=0.001). Conclusions: Patients with trigonal tumours, variant histology, and nodal involvement are more likely to have gynecological organ invasion at RAAE. This information may help improve counselling of patients and better identify candidates for gynecological organsparing cystectomy.